1998
DOI: 10.1074/jbc.273.8.4378
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Extrinsic Pathway Factor Xa Formation by Tissue Factor Pathway Inhibitor

Abstract: ؊1⅐s ؊1 ) that was substantially greater than the value (7.34 ؎ 0.8 ؋ 10 6 M ؊1 ⅐s ؊1 ) directly measured. Thus, VIIa⅐TF is inhibited at near diffusion-limited rates by Xa⅐TFPI formed during catalysis which cannot be explained by studies of the isolated reaction. We propose that the predominant inhibitory pathway during factor X activation may involve the initial inhibition of factor Xa either bound to or in the near vicinity of VIIa⅐TF on the membrane surface. As a result, VIIa⅐TF inhibition is unexpectedly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
224
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(233 citation statements)
references
References 49 publications
7
224
0
2
Order By: Relevance
“…Computational analysis of the full-length deduced amino acid sequences suggested that Seq7 was homologous to TFPI, a Kunitz-type protein, possessing 3 KPI domains, which is involved in the regulation of blood coagulation by inhibiting FXa and FVIIa. 34 Seq7 contains a domain with homology to the KPI domain 1. Therefore, Seq7 might inhibit factors in the vertebrate coagulation cascade such as FVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…Computational analysis of the full-length deduced amino acid sequences suggested that Seq7 was homologous to TFPI, a Kunitz-type protein, possessing 3 KPI domains, which is involved in the regulation of blood coagulation by inhibiting FXa and FVIIa. 34 Seq7 contains a domain with homology to the KPI domain 1. Therefore, Seq7 might inhibit factors in the vertebrate coagulation cascade such as FVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…The zymogen preparation was depleted of traces of active Xa as described (26). Factor X was proteolytically activated to factor Xa using the purified X activator isolated from Russell's viper venom and further purified by affinity chromatography on benzamidine-Sepharose (27).…”
Section: Methodsmentioning
confidence: 99%
“…All kinetic studies were performed in 20 mM Hepes, 0.15 M NaCl, 5 mM CaCl 2 , 0.1% (w/v) PEG-8000, pH 7.50 (designated as Assay Buffer). Continuous and discontinuous kinetic studies were performed using 96-well plates (Corning 9710, Corning, NY) pretreated with Tween 20 and air-dried prior to use as described previously (26) to minimize adsorption artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…The second Kunitz domain binds first to a molecule of FXa and deactivates it. The first domain then rapidly binds to an adjacent TF-FVIIa complex, preventing further activation of Factor X [40][41][42]. The formation of this quaternary compound is necessary for the inhibitory action of TFPI on the TF-FVIIa complex.…”
Section: ó 2004 Blackwell Publishing Ltdmentioning
confidence: 99%